2006
DOI: 10.1038/sj.emboj.7601016
|View full text |Cite
|
Sign up to set email alerts
|

The role of receptor internalization in CD95 signaling

Abstract: Activation of the cell surface CD95 receptor triggers a cascade of signaling events, including assembly of the death-inducing signaling complex (DISC), that culminate in cellular apoptosis. In this study, we demonstrate a general requirement of receptor internalization for CD95 ligand-mediated DISC amplification, caspase activation and apoptosis in type I cells. Recruitment of DISC components to the activated receptor predominantly occurs after the receptor has moved into an endosomal compartment and blockade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
239
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(262 citation statements)
references
References 50 publications
(61 reference statements)
17
239
2
4
Order By: Relevance
“…Ezrin-actin association is reported to be required for endocytosis of Fas in mouse embryonic fibroblasts and L12.10 cells (Piazzolla et al, 2005;Chakrabandhu et al, 2007Chakrabandhu et al, , 2008. We found that Fas internalization in H9 cells ( Figure 6) was similar in efficiency to that documented elsewhere (Piazzolla et al, 2005;Lee et al, 2006;Chakrabandhu et al, 2007). However, deficiency in ezrin did not affect endocytosis of Fas in H9 cells, suggesting that the observed enhanced DISC formation (Figure 7) was not due to altered internalization of Fas.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Ezrin-actin association is reported to be required for endocytosis of Fas in mouse embryonic fibroblasts and L12.10 cells (Piazzolla et al, 2005;Chakrabandhu et al, 2007Chakrabandhu et al, , 2008. We found that Fas internalization in H9 cells ( Figure 6) was similar in efficiency to that documented elsewhere (Piazzolla et al, 2005;Lee et al, 2006;Chakrabandhu et al, 2007). However, deficiency in ezrin did not affect endocytosis of Fas in H9 cells, suggesting that the observed enhanced DISC formation (Figure 7) was not due to altered internalization of Fas.…”
Section: Discussionsupporting
confidence: 69%
“…Internalization of Fas is required for efficient DISC formation and caspase-8 activation (Lee et al, 2006;Chakrabandhu et al, 2007). Ezrin-actin association is reported to be required for endocytosis of Fas in mouse embryonic fibroblasts and L12.10 cells (Piazzolla et al, 2005;Chakrabandhu et al, 2007Chakrabandhu et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations